Discourse Analysis of Substantive Democracy in Anies Baswedan’s Dialogue with UGM Students: Analisis Diskursus Demokrasi Substansial dalam Dialog Anies Baswedan dengan Mahasiswa UGM - Rizki Fauzan Yusuf (Yayasan Cerdas Pedia Indonesia, 2025)
This study analyzes the dialogue between Anies Baswedan and Universitas Gadjah Mada students as a microcosm of Indonesia’s post-Reformasi democratic paradox. Employing Teun A. van Dijk’s Critical Discourse Analysis, the research examines three discourse dimensions: textual structure, social cognition, and social context. Primary data from the dialogue transcript were analyzed to identify core themes: institutional crisis (KPK and Constitutional Court), youth economic justice and welfare, identity-based political polarization, and quality of civic space and meaningful public participation. Findings reveal that student questions act as a civil society “watchdog” mechanism, demanding a shift from procedural to substantive democracy. The politician’s responses expose tensions between procedural rhetoric and substantive needs, reflecting challenges in institutional reform, welfare distribution, social cohesion, and civil liberties. The paper underscores the role of youth as democratic change agents and recommends more meaningful participation channels to strengthen Indonesia’s democratic legitimacy.